(3(cos14^@+isin14^@))/(2(cos121^@+isin121^@)3(cos14∘+isin14∘)2(cos121∘+isin121∘)
= 3/2xx((cos14^@+isin14^@))/((cos121^@+isin121^@))xx((cos121^@-isin121^@))/((cos121^@-isin121^@)32×(cos14∘+isin14∘)(cos121∘+isin121∘)×(cos121∘−isin121∘)(cos121∘−isin121∘)
= 3/2(cos14^@cos121^@-i^2sin14^@sin121^@-icos14^@sin121^@+isin14^@cos121^@)/(cos^2 121^@-i^2sin121^@)32cos14∘cos121∘−i2sin14∘sin121∘−icos14∘sin121∘+isin14∘cos121∘cos2121∘−i2sin121∘
= 3/2(cos14^@cos121^@+sin14^@sin121^@+i(sin14^@cos121^@-cos14^@sin121^@))/(cos^2 121^@+sin121^@)32cos14∘cos121∘+sin14∘sin121∘+i(sin14∘cos121∘−cos14∘sin121∘)cos2121∘+sin121∘
= 3/2(cos(14^@-121^@)+isin(14^@-121^@))/132cos(14∘−121∘)+isin(14∘−121∘)1
= 3/2(cos(-107^@)+isin(-107^@))32(cos(−107∘)+isin(−107∘))
= 3/2(cos107^@-isin107^@)32(cos107∘−isin107∘)